Aspirin Reduces the Potentiating Effect of CD40L on Platelet Aggregation via Inhibition of Myosin Light Chain - Kojok, Kevin (J Am Heart Assoc, 2020)
BACKGROUND: Antiplatelet therapy with aspirin (acetylsalicylic acid [ASA]) is less efficient in some coronary patients, which increases their risk of developing thrombosis. Elevated blood levels of thromboinflammatory mediators, like soluble CD40L (sCD40L), may explain such variabilities. We hypothesized that in the presence of elevated levels of sCD40L, the efficacy of ASA may vary and aimed to determine the effects of ASA on CD40L signaling and aggregation of platelets. METHODS AND RESULTS: The effects of ASA on CD40L‐treated human platelets, in response to suboptimal concentrations of collagen or thrombin, were assessed at levels of aggregation, thromboxane A(2) secretion, and phosphorylation of p38 mitogen‐activated protein kinase, nuclear factor kappa B, transforming growth factor‐β–activated kinase 1, and myosin light chain. sCD40L significantly elevated thromboxane A(2) secretion in platelets in response to suboptimal doses of collagen and thrombin, which was reversed by ASA. ASA did not inhibit the phosphorylation of p38 mitogen‐activated protein kinase, nuclear factor kappa B, and transforming growth factor‐β–activated kinase 1, with sCD40L stimulation alone or with platelet agonists. sCD40L potentiated platelet aggregation, an effect completely reversed and partially reduced by ASA in response to a suboptimal dose of collagen and thrombin, respectively. The effects of ASA in sCD40L‐treated platelets with collagen were related to inhibition of platelet shape change and myosin light chain phosphorylation. CONCLUSIONS: ASA does not affect platelet sCD40L signaling but prevents its effect on thromboxane A(2) secretion and platelet aggregation in response to collagen, via a mechanism implying inhibition of myosin light chain. Targeting the sCD40L axis in platelets may have a therapeutic potential in patients with elevated levels of sCD40L and who are nonresponsive or less responsive to ASA.